Analisis Pengaruh Kualitas Produk terhadap Kepuasan Pelanggan pada Usaha Pangan “Warunge Indah” Jakarta - Sudiharto Sudiharto; Kusairi Kusairi; Benny Hari Kusuma (Jurnal Syntax Transformation, 2021)
The development of the business field has been colored by various kinds of competition in all fields, including in the field of food, technology and communication. Good quality and quality service will tend to provide more satisfaction to customers who use services in the company. The purpose of this study is to analyze the influence of product quality on customer satisfaction on the food business "Warunge Indah" Jakarta. The study uses descriptive research with qualitative approaches, data collection and analysis methods using interviews and observations. The results of the study explained that the “Indah Warunge” has provided product quality in accordance with the rules that apply in the company. Products that are sold various foods and healthy drinks even bitter black honey also exist. The conclusion obtained from the research that customers who buy “Indah Warunge” products are satisfied with the quality of products sold by “Indah Warunge”.